2014
DOI: 10.1200/jco.2013.54.6861
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of Rituximab for the Treatment of Diffuse Large B-Cell Lymphoma (II): Extended Rituximab Exposure Time in the SMARTE-R-CHOP-14 Trial of the German High-Grade Non-Hodgkin Lymphoma Study Group

Abstract: Extended rituximab exposure compared with eight 2-week applications in combination with 6×R-CHOP-14 significantly improved outcome of elderly poor-prognosis patients without increasing toxicity. To our knowledge, results obtained with the SMARTE-R-CHOP-14 rituximab schedule are the best reported for elderly patients with DLBCL to date. In the subgroup of poor-prognosis patients treated with extended rituximab exposure, the outcome seemed superior to that of a similar historical cohort of patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 15 publications
3
66
0
3
Order By: Relevance
“…10 These results are attributed to higher rituximab clearance in males who are undertreated without rituximab maintenance. 11 The risk of relapse at onset (age-adjusted International Prognostic Index) or disease status after induction (CR or PR) would also affect the applicability of rituximab maintenance and should be clarified.…”
mentioning
confidence: 89%
“…10 These results are attributed to higher rituximab clearance in males who are undertreated without rituximab maintenance. 11 The risk of relapse at onset (age-adjusted International Prognostic Index) or disease status after induction (CR or PR) would also affect the applicability of rituximab maintenance and should be clarified.…”
mentioning
confidence: 89%
“…Die Optimierung der Gaben von Rituximab wird zurzeit von der DSHNHL untersucht [45]. Durch Genexpressionsanalyse konnten 2 Subtypen des DLBCL identifiziert …”
Section: Introductionunclassified
“…We further demonstrated that FcgRIIIA-158VF polymorphism influenced the rituximab pharmacokinetics/ pharmacodynamics relationship, homozygous VV NK cells needing 4 times lower RTX concentration compared with homozygous FF NK cells to obtain a comparable in vitro effect, 40 suggesting that certain subsets of patients may benefit from increased dosing. Further studies demonstrated that PK-guided RTX dosing to maintain sufficient RTX concentrations in indolent non-Hodgkin lymphomas (iNHLs), 41 or an increased number of RTX infusions in DLBCL, 42 failed to demonstrate any clinical advantage. As suggested in a murine model, 43 antigen burden is probably, at least in DLBCL, the main parameter affecting RTX exposure.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…44 The theoretical dose of RTX according to tumor burden could be calculated, demonstrating that the optimal dose was close to the approved dose, probably explaining the lack of significant difference in a dose-dense trial. 42 The correlation of total metabolic volume before treatment with distribution volumes (V D ) without modification of clearance could suggest a "sponge effect," tumor cells trapping RTX before release of the antibody after exerting its cytotoxic effect. 44 In CLL patients, the standard dose of RTX is higher than in non-Hodgkin lymphoma (NHL) patients (500 mg/m 2 instead 375 mg/m 2 ), justified by a faster RTX clearance observed in the first phase 2 trial, 37,39 leading to low RTX exposure and a worse outcome.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%